Review of development and characterization of sugar palm fiber–reinforced polymer composites - Sahari, J.; Maleque, Md. Abdul; Sapuan, S.M.; Ishak, M.R.; Suriani, M.J.; YUsriah, L. (CRC Press, 2019)
This chapter reviews the characterization and development of SPF- reinforced polymer composites, as well as other important issues related to these composites. Sugar palm fiber has been the subject of research to study the potential of this fiber as an alternative option to reinforce polymer composites due to the fiber’s good mechanical strength and its stiffness, as well as its high durability and good resistance to sea water, all of which make this fiber a potential alternative to synthetic fiber in polymer composites. Works have been carried out to study the physical, mechanical, and thermal properties of of understand the nature of this fiber, the suitable manufacturing parameters to produce good composites from this fiber, and the opportunities that SPF fiber could offer. The works are not limited only to basic mechanical and thermal properties of SPF, but also study the tribological performance durability, biodegradability, and compatibility of the SPF and its composites.